Indonesia's fiscal capacity and burden-sharing scheme: A new insight from handling COVID-19 - Pihri Buhaerah; Nur Firdaus (Asian Development Bank Institute (ADBI), 2023)
The spread of COVID-19 has brought many economies into recession, and Indonesia is no exception. In response to the adverse impacts of the COVID-19 pandemic, a higher fiscal stimulus is needed to achieve economic recovery. However, as one of the world's most populous countries, Indonesia has struggled with limited financial resources, leading to a significant budget deficit. Although the government has addressed this issue through a burden-sharing scheme with the Central Bank, the public is still wary about Indonesia's macroeconomic stability and fiscal sustainability. This study will challenge the household budget analogy by arguing that fiscal deficit is not evidence of overspending. Also, it is argued that the burden-sharing scheme would not cause any negative macroeconomic consequences. Instead, a higher accumulation of external debt-denominated foreign currency is regarded as the primary source of potential macroeconomic instability. We explain that running a fiscal deficit will boost the economy, restore household consumption, and increase private revenue. In this context, the role of the central bank is crucial under the fiscal deficit regime because it absorbs all government bonds in the market as a part of the monetary operation. Hence, if the role of the central bank is not isolated in macroeconomic analysis, the government budget is different from the household or firm budget analogy. In other words, a fiscal deficit is a typical phenomenon not only during wartime or recession but also during peacetime or expansion. Thus, the option to issue new government securities and sell them directly to the central bank provides more economic security than external debt finance.
Keywords: E5; E62; E12; 330; fiscal deficit; burden-sharing scheme; household budget analogy; debt-monetization; fiscal sustainability; stock-flow consistent model